Extended longevity at high altitude: Benefits of exposure to chronic hypoxia - Gustavo R Zubieta-Calleja; Natalia A Zubieta-DeUrioste (Wolters Kluwer Medknow Publications, 2017)
BACKGROUND: Acute exposure to hypobaric hypoxia can give rise to acute mountain sickness, and rarely, high altitude pulmonary edema, and high altitude cerebral edema. However, with gradual adaptation to "chronic hypoxia", following the Adaptation to High Altitude Formula (Adaptation = time / altitudeΔ), the organism does remarkably well. High altitude residents are perfectly adapted to their environment. The cities of La Paz (3100-4100 m) and El Alto (4100 m) stand as living proof of this with 2.7 million inhabitants living perfectly normal lives, undisturbed by hypoxia and most even unaware of its existence. All the cells of the organism adapt to a lower arterial oxygen arterial partial pressure (PaO2) and likewise to a lower arterial partial pressure of carbon dioxide (PaCO2), an essential component that linked to an increased compensatory hemoglobin explain the paradox of increased "tolerance to hypoxia" at high altitude. METHODS: We reviewed the > 70 years old population historic records of the official Bolivian registration service SEGIP. Two groups were analyzed: those greater than 90 years of age, and those greater than 100 years of age according to the different altitude departments in Bolivia. RESULTS: As the altitude increases, the longevity increases. Santa Cruz at 416m and La Paz at 3800m (average), both with around 2.7 million inhabitants each, have 6 versus 48 centenarians respectively. CONCLUSIONS: Life under chronic hypoxia is not only tolerable, but also is, in fact, favorable to improve or treat many pathological conditions such as asthma, coronary artery disease, obesity and even giving rise to improved longevity. Sea level residents (when compared to high altitude residents) suffer a disability: poor tolerance to hypoxia.